1990
DOI: 10.1016/s0886-3350(13)80870-x
|View full text |Cite
|
Sign up to set email alerts
|

Development, advantages, and methods of the continuous circular capsulorhexis technique

Abstract: The development of the continuous circular capsulorhexis (CCC) technique has contributed significantly to the safety and effectiveness of cataract extraction and intraocular lens implantation. This technique facilitates every size of smooth, circular, capsular opening, and it produces a strong capsular rim that resists tearing even when stretched during lens material removal or lens implantation. Maintaining the general integrity of the eye and facilitating such procedures as hydrodissection, endolenticular ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
124
0
18

Year Published

1990
1990
2006
2006

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 502 publications
(142 citation statements)
references
References 2 publications
0
124
0
18
Order By: Relevance
“…However, an incomplete capsulorhexis undoubtedly increases significantly the risk of posterior capsule rupture and its associated sequelae. 1 Of concern, in all six cases the attending surgical and anaesthetic teams were uncertain of the cause of the ocular deviation. A retrospective review of the anaesthetic charts revealed that all six patients had undergone GA with spontaneous respiration techniques without effective NDMR.…”
Section: Introductionmentioning
confidence: 96%
“…However, an incomplete capsulorhexis undoubtedly increases significantly the risk of posterior capsule rupture and its associated sequelae. 1 Of concern, in all six cases the attending surgical and anaesthetic teams were uncertain of the cause of the ocular deviation. A retrospective review of the anaesthetic charts revealed that all six patients had undergone GA with spontaneous respiration techniques without effective NDMR.…”
Section: Introductionmentioning
confidence: 96%
“…An intact complete CCC is critical to minimize the risk of capsular tear and to ensure stable in-the-bag intraocular lens (IOL) implantation. 1 Various dyes include fluorescein, 2-4 indocyanine green, 2,5-8 and trypan blue, 2,9-16 have been used for capsular staining to facilitate CCC. Different staining techniques, including subcapsular injection, staining under an air bubble, and staining under viscoelastic material, have been attempted.…”
Section: Introductionmentioning
confidence: 99%
“…Successful completion of this step is associated with low complication rates and good surgical outcomes. 2 This has been attributed to the inherent strength and elasticity of the continuous curvilinear capsulorrhexis. 2 Recently, staining of the anterior capsule for difficult capsulorrhexis because of poor visibility from inadequate retro-illuminated red reflexes has become popular with cataract surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…1 The absence of an adequate red reflex makes it difficult to perform continuous curvilinear capsulorrhexis with certainty. 2 Retroillumination created by coaxial light from the operating microscope is reduced in the presence of a dense cataract and in heavily pigmented fundi. Various methods to overcome this problem have been described and recently dye staining of the anterior capsule has been employed.…”
Section: Introductionmentioning
confidence: 99%